From reporters to influencers analyzing the impact of self-promotion on journalistic integrity in the contemporary digital media landscape - Malimban, Joash Edric S.; Ilagan, Karol; University of the Philippines Diliman College of Media and Communication (Quezon City University of the Philippines Diliman, 2025)
This study investigates the evolving relationship between self-promotion strategies and journalistic integrity within the rapidly changing digital media landscape of the Philippines. Building upon existing scholarship highlighting the challenges of maintaining traditional journalistic values in the face of new technologies (Bennett Iyengar, 2008: Hermida, 2012: Ward, 2017). this research examines how the increasing pressure to cultivate personal brands and attract online engagement through self-promotion impacts core journalistic principles. The study employs a mixed-methods approach, combining quantitative content analysis of Facebook posts from three prominent Filipino independent digital journalists with qualitative thematic analysis of semi-structured interviews. The quantitative analysis assesses the frequency and types of self-promotion strategies employed (Personal Branding, Professional Promotion, Audience Engagement, Lifestreaming, Fame by Association), thematic content focus, and audience engagement metrics. The qualitative analysis. informed by Critical Discourse Analysis (CDA), explores the journalists' motivations for self-promotion, their perspectives on the ethical dilemmas involved, and their assessments of the broader impact of social media on journalistic practices.

The findings reveal a complex interplay between self-promotion strategies and core journalistic values. While self-promotion offers opportunities to build audiences, establish credibility, and address the precarious financial realities facing many journalists. particularly freelancers (Ward, 2017), it also raises significant ethical concerns. The analysis identifies instances of Role Conflict, where the lines between personal branding and professional responsibilities blur, potentially undermining journalistic objectivity. Further, the study highlights instances of Objectivity/Bias, where the pursuit of engagement and the affordances of social media platforms may lead to a prioritization of opinion and advocacy over balanced reporting, potentially amplifying existing societal biases (Bennett & Iyengar, 2008). Moreover, challenges related to Accuracy/Verification emerge, underscoring the difficulties of maintaining rigorous fact-checking standards in a rapidly evolving information ecosystem characterized by the spread of misinformation (Pew Research Center, 2023). The algorithmic filtering effects of social media platforms, often rewarding sensationalism and emotionally charged content (Pariser, 2011), further exacerbate these challenges.

This research contributes to the growing body of literature exploring the ethical dimensions of online journalism by providing a nuanced understanding of how self-promotion strategies influence journalistic practices in the Philippine context. The study's findings have significant implications for journalists, news organizations. journalism educators, and policymakers. The need for updated ethical guidelines and robust media literacy initiatives is underscored, reflecting the broader societal concerns regarding the erosion of trust in traditional media and the rise of misinformation in the digital age (Pew Research Center, 2023). This study provides a foundation for future research exploring the long-term impacts of self-promotion on journalistic integrity, the influence of algorithmic systems on journalistic practices, and the development of effective strategies for countering disinformation and fostering a more ethical and sustainable media landscape. Furthermore, this research adds to the understanding of the specific challenges faced by journalists in navigating the digital media environment while adhering to the fundamental principles of journalistic ethics as articulated in established codes of conduct (Christians et al., 2009). By examining these issues through a comparative case study approach, the study offers practical guidance for navigating the ethical tightrope of self-promotion in the increasingly complex and rapidly evolving media landscape. The study's findings thus contribute significantly to both theoretical understandings of digital journalism and the development of practical recommendations for navigating the ethics of the evolving online media environment.
Thesis
Includes bibliography
Keywords: Self-publishing -- Philippines; Online journalism -- Philippines; Internet personalities -- Philippines; Journalism -- Philippines -- Moral and ethical aspects